Stochastic Sizing of Energy Storage Systems for Wind Integration - Le, D. D.; Nguyen, N. T. A. (Engineering, Technology & Applied Science Research, 2018)
In this paper, we present an optimal capacity decision model for energy storage systems (ESSs) in combined operation with wind energy in power systems. We use a two-stage stochastic programming approach to take into account both wind and load uncertainties. The planning problem is formulated as an AC optimal power flow (OPF) model with the objective of minimizing ESS installation cost and system operation cost. Stochastic wind and load inputs for the model are generated from historical data using clustering technique. The model is tested on the IEEE 39-bus system.